(untitled) (Bangladesh Journal of Otorhinolaryngology, 2021)
Background: Conventional surgeries of the nasal septum improve the nasal airway but recent development and advancement of the knowledge about the endoscopic septoplasty has significantly changed the treatment modality and had brought focus over several aspects of possible advantages. This study aims to see the advantages, complications and limitations of endoscopic septoplasty. Methods: It was an observational prospective study conducted over 90 patients of symptomatic deviated nasal septum. It evaluated symptoms, anterior rhinoscopy and nasal endoscopy findings, objective and subjective improvement of symptoms using the nasal obstruction symptom evaluaiton (NOSE) score, post-operative pain using the visual analogue scale (VAS) and complication following the surgery. Results: Deviated nasal septum (DNS) either left or right side was the most common examination finding 97.78%. Post-operatively there was a good symptom relief and significant subjective improvement in NOSE scores with average decline in the score by 96.26%. Objective assessment of all patients showed improved airway. The complication rate was minimum 7.78%. Conclusion: Endoscopic septoplasty (ES) was found to have distinct advantages with good subjective and objective improvement of symptoms and lesser rate of complications. It should be an option offered to all patients requiring septoplasty. We also found that it helps in improving the learning curve and surgical skill of the trainees. Bangladesh J Otorhinolaryngol 2021; 27(2): 170-176